BIM in principle and in practice - Barnes, Peter, 1954- (ICE Publishing, 2019)
BIM in Principle and in Practice, now in its third edition, is a guide to BIM principles and techniques. It provides clear explanations of core concepts, and answers many of the common questions that are asked about BIM. It offers a straightforward overview of BIM fundamentals in simple language, with clear explanations of how BIM is used at each stage of a construction project. Coverage includes: core concepts, benefits of using BIM, examples of BIM in practice, design liability and ownership, collaboration and contracts, and insurance. Thoroughly revised, this edition includes detailed coverage of current standards (BSI, PAS and ISO), new case studies, the UK Government's 2016 Building Information Modelling mandate, consolidated recommendations of the EU BIM Task Group, and future directions including consideration of potential changes to EU Procurement rules following Brexit.